Model Pembelajaran Homeschooling Pendidikan Anak Usia Dini - Noor Padilah; Reni Rulita; Renny Yuniar; Nita Priyanti; Nor Annisa (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Homeschooling has now become an option for the parent to educate the child. The cause is because of the negative news that accessed regarding formal education, this reduces the confidence of parents towards formal education. There are advantages and disadvantages of homeschooling. The data collection technique used by the author in this study is a literature study, namely by searching for data related to the discussion in the title of the research that the researcher took. In this study, relevant data were collected in various ways, namely by Literature Studies, Literature Studies, and Internet searches. Data Analysis Techniques The research is carried out using qualitative analysis techniques in a deductive way, which means from things or theories that are general in nature to draw conclusions that are specific. Homeschooling has become a trend in big cities in Indonesia. From this phenomenon, it can be estimated that homeschooling is increasingly needed by the community. At least the existence of homeschooling will fulfill about 10% of the total number of children in Indonesia.